Serum markers in alkaptonuria: simultaneous analysis of homogentisic acid, tyrosine and nitisinone by liquid chromatography tandem mass spectrometry. (September 2015) - Hughes, Andrew T; Milan, Anna M; Davison, Andrew S; Christensen, Peter; Ross, Gordon; Gallagher, James A; Dutton, John J; Ranganath, Lakshminarayan R
Background: Alkaptonuria is a rare debilitating autosomal recessive disorder of tyrosine metabolism, where deficiency of homogentisate 1, 2-dioxygenase results in increased homogentisic acid. Homogentisic acid is deposited as an ochronotic pigment in connective tissues, especially cartilage, leading to a severe early onset form of osteoarthritis, increased renal and prostatic stone formation and hardening of heart vessels. Treatment with the orphan drug, nitisinone, an inhibitor of 4-hydroxyphenylpyruvate dioxygenase has been shown to reduce urinary excretion of homogentisic acid. Method: A reverse phase liquid chromatography tandem mass spectrometry method has been developed to simultaneously analyse serum homogentisic acid, tyrosine and nitisinone. Using matrix-matched calibration standards, two product ion transitions were identified for each compound (homogentisic acid, tyrosine, nitisinone) and their respective isotopically labelled internal standards ( 13 C6 -homogentisic acid, d2 -tyrosine, 13 C6 -nitisinone). Results: Intrabatch accuracy was 94–108% for homogentisic acid, 95–109% for tyrosine and 89–106% for nitisinone; interbatch accuracy (n = 20) was 88–108% for homogentisic acid, 91–104% for tyrosine and 88–103% for nitisinone. Precision, both intra- and interbatch were <12% for homogentisic acid and tyrosine, and <10% for nitisinone. Matrix effects observed with acidified serum were normalized by the internal standard (<10% coefficient of variation). Homogentisic acid, tyrosine and nitisinone proved stable after 24 h at room temp, three freeze–thaw cycles and 24 h at 4℃. The assay was linear to 500μmol/L homogentisic acid, 2000μmol/L tyrosine and 10μmol/L nitisinone; increased range was not required for clinical samples and no carryover was observed. Conclusions: The method developed and validated shows good precision, accuracy and linearity appropriate for the monitoring of alkaptonuria patients, pre- and post-nitisinone therapy.